2016
DOI: 10.1136/bmjopen-2016-012127
|View full text |Cite
|
Sign up to set email alerts
|

Extent and pattern of burden of care and its associated factors among Eritrean families of persons living with schizophrenia: a cross-sectional study

Abstract: PurposeTo assess the caregiving burden and its associated factors among Eritrean families of persons living with schizophrenia.MethodsA cross-sectional study was conducted for 146 caregivers with their respective known patients with schizophrenia of Saint Mary's Neuropsychiatric National Referral Hospital (SMNNRH). Data were collected using Pai and Kapur's Family Burden Interview Schedule (FBIS), the Positive and Negative Syndrome Scale (PANSS) and self-prepared sociodemographic sheet. Data were analysed using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 28 publications
7
12
0
Order By: Relevance
“…This study also found out that the higher the caregivers’ income, the lower the caregiver burden. This was in agreement with previous studies [11, 31]. As previous studies stated that most of the patients were economically dependent on a family member [32] and higher degree of burden on the caregivers were associated with low income [33].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This study also found out that the higher the caregivers’ income, the lower the caregiver burden. This was in agreement with previous studies [11, 31]. As previous studies stated that most of the patients were economically dependent on a family member [32] and higher degree of burden on the caregivers were associated with low income [33].…”
Section: Discussionsupporting
confidence: 93%
“…Our study found out that caregiving burden increases as age of the caregiver increases. This finding is in accordance with previous studies that suggested older caregivers experience higher levels of caregiving burden compared to their younger counterparts [11, 29, 30]. Older caregiver cannot deliver care accordingly and are worried about who will take over their caregiving roles when they are no longer alive [30].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These findings are comparable with different study worldwide. 16,20,24,25 The study has some limitations. The participants were from specific geographical region so generalization of the result to other areas is difficult.…”
Section: Discussionmentioning
confidence: 99%